Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{2000}{2001}=1-\frac{1}{2001}<1-\frac{1}{2002}=\frac{2001}{2002}\)
1 - 2000/2001 = 1/2001 ; 1 - 2001/2002 = 1/2002
2000/2001 < 2001/2002
A = 2003 × 2002 - 2/2001 × 2003 + 2001
A = 2003 × (2001 + 1) - 2/2001 × 2003 + 2001
A = 2003 × 2001 + (2003 - 2)/2001 × 2003 + 2001
A = 2003 × 2001 + 2001/2001 × 2003 + 2001
A = 1
a) 2001 x 757 + 2002 x 233
= 2001 x 757 + (2001 + 1) x 233
= 2001 x 757 + 2001 x 233 + 1 x 233
= 2001 x (757+233) + 233
= 2001 x 1000 + 233
= 2001000 + 233
= 2001233
a) 2001x757+2002x243
=2001 x 757+ (2001+1) x233
=2001 x757+2001x233+1 x233
=2001x(757+233)+233
=2001x1000 +233
=201000+233
=2001233
b)(m:1-m x1):(mx2001+m+1)
=(m-m):(mx2001+m+1)
=0:(mx2001+m+1)
=0
Học tốt
khó thế tôi ko làm được
???????????????????????????????????????????